SPATIAL-TEMPORAL ANALYSIS OF FOREST DEFORESTATION IN LORE-LINDU NATIONAL PARK - Adam Malik; Nitya Ade Santi; Misra Misra; Hamka Hamka (Universitas Tadulako, 2023)
Indonesia is listed as one of the countries with a high rate of deforestation. This deforestation occurs in almost all islands in Indonesia, including Sulawesi. Deforestation analysis needs to be carried out to determine the rate of change in forest cover and the factors that cause it, so that forms of forest management can be planned to achieve sustainable forest management This analysis is expected to fulfill the need for information on how the vulnerability of deforestation occurs spatially, where the locations of deforestation occur and what factors encourage deforestation and forest degradation. The study found that the rate of forest decrease from 1990 to 2020 was 328 hectares/year with the highest rate was from 1990 to 2000 with rate of forest decrease 690 hectares/year. The deforestation located in four area that has difference land cover change. Area 1 changed to settlement and dry land agriculture, area 2 changed to cocoa plantation by the local community planted in 2000s, area 3 changed to cocoa plantation by the local community planted in 2010s. Area 4 changed to open area/bareland indicated after ilegal logging occurred since 2000.